Leadership Effective, Work Ethic, and Collective Relation on The Organizational Commitment (Empirical Study at Junior High Schools in Minahasa Regency) - Dehoop, Sem Simson (AIBPM Publisher, 2019)
This research aims were analyzing the influence of leadership effectiveness, work ethic and collective relations toward organizational commitment, of the teachers at Junior High Schools in Minahasa Regency. The data were collected from a randomly selected 90 samples from the total population unit of 902 employees. Survey method uses path analysis to analyze data descriptively and inferentially. The findings show that: (1) a positive direct influence of leadership effectiveness on the organizational commitment, (2) a positive direct influence of work ethic on organizational commitment, (3) a positive direct influence of collective relations on organizational commitment, (4) a positive direct influence of collective relations on organizational commitment. The findings recommend that to improve organizational commitment needs to enhance leadership effectiveness, work ethic and collective relations.